Parameter Sensitivity Analysis of Natural Frequency of a Two Branch Herringbone Gear Transmission System - Zhang Quanqing; Wang Sanmin; Zhao Chunyang; Ma Yaohui; Ren Hongfei (Jixie chuandong)
Parameter sensitivity values of natural frequency of the two branch herringbone gear drive system commonly used in a high-power ship are calculated,and the influence of structural parameters such as meshing stiffness,moment of inertia and manufacturing error on natural frequency of the transmission system is obtained. The torsional dynamic model of the branched drive is established, the vibration mode characteristics of the branched drive are verified by finite element analysis, the parameter sensitivity expression under multi-excitation is deduced by the mode method, and it is applied to the stability analysis of the two-branched herringbone gear drive system. Then, according to the sensitivity value calculated theoretically and the actual working conditions, by optimizing the structure of the transmission system, the modified scheme obtained by this method significantly improves the vibration resistance of the gear train, and through an example, it is found that the key parameters obtained by this analysis method have obvious effect on anti-vibration and noise reduction of the system. This analysis method can also be used in vibration and noise reduction design of other types of branch drives.